Analysis and Perspectives of the Sugarcane Industry: A Key Activity for Rural Development in Morelos State - Torres, Fernando Romero; Pérez Mayo, Augusto Renato; Mark, Ricardo Orosco (New Innovations in Economics, Business and Management Vol. 6, 2022)
The objective is to analyze the evolution of the sugar industry as a business influenced by a strong social burden. It is essential to analyze its history and evolution to understand its present situation and to be able to predict its future as an option for business for the tropical areas of the world and specifically for the state of Morelos. Sugarcane industry represents a predominant activity in the economy of Mexico and Morelos state. As such, it represents a key element for the development of families, the state, and rural environment. The present study approaches this perspective from normative and organizational scopes, the industry evolution, and outcomes during the second decade of the 20th century. This paper develops from research in books and articles in order to identify the main historical events that shaped this economical area, followed by a revision of the main laws and norms that regulate it and placed it as predominant from an economic and social perspective. Subsequently, we analyze its organizational conformation as a dynamic identity that affects its operation and explains its effects. For such purpose, we carried out interviews (50) applied to key participants in the sugar cane sector at state level. Lastly, we study the market and sector prospects by using statistics and future projections developed by national and international agencies specialized in economy. We conclude that the sugarcane industry needs to diversify its products so that the sector could incorporate in markets that respond to the consumption needs of this kind of food. Moreover, the adequate investment is essential in order to satisfy the productivity and quality needs that the market requires. These resources should come from the cash flows generated through sales and should allow the usage of regulatory and organizational benefits provided by its position as a strategic industry.